Renal Transplant Pathology Serie Kidney allograft interstitial fibrosis and tubular atrophy (IFTA) due to specific causes: : Polyomavirus nephropathy - Mubarak, Muhammed (Pakistan Journal of Kidney Diseases, 2023)
NA